STUDI POLA TANAM PADA LAHAN PASANG SURUT TIPE C DI DESA TRI MULYA AGUNG KECAMATAN LALAN KABUPATEN MUSI BANYUASIN - Khoirudin, Isa; Abubakar, Rafeah; Kurniawan, Rahmat (Muhammadiyah University of Palembang, 2016)
Study of Planting Patten On Tidal Land Type C in Tri Mulya Agung village, Lalan district, Musi Banyuasin Regance. This research purpose to knowh how to plantig pattern on tidal land of type C in Tri Mulya Agung village, Lalan district, Musi Banyuasin Regance and to know income of farmers in Tri Mulya Agung village, Lalan district, Musi Banyuasin Regance for one year. The research has been done in Tri Mulya Agung village, Lalan district, Musi Banyuasin regance in May-July, 2016. The method used in this research is survey method, sampling method used in this research is simple random sampling, data collection methods used in this research were interviews and observations of farmers instance in coherent with questions which has been prepared. The results of the research show that planting was worked by farmers in the Tri Mulya Agung consists of two tipys of planting patterns that monoculture and bikultur. the income received by farmers that apply monoculture is Rp 14,747,500.00 Lg/th. While the magnitude of the income received by farmers from farming implement planting pattern bikultur Rp 24,627,147.00 Lg / th.